Soft contact lenses for keratoconus: case report - González-Méijome, José Manuel (2006)
Contact lenses have assisted the refractive correction of keratoconus since the 19th century. In these case reports, the authors describe their experience with a new soft contact lens design. METHODS: The Soft K is a new soft lens comprising a thick fenestrated design to fit in patients with mild to moderate corneal distortion and fitting problems or physical intolerance to rigid gas-permeable (RGP) contact lenses. Three eyes with mild keratoconus from two 25-year-old patients (one man and one woman) were fitted with the Soft K contact lens. Both patients had previously worn other contact lens types. RESULTS: Improvements in comfort and quality of vision compared with previously worn RGP or soft toric contact lenses were the most remarkable advantages objectively observed and subjectively described by both patients. For one patient, a professional soccer player, the benefits were also important in terms of compatibility with the dynamic environment of his activity, satisfying the need for stable correction and constant full field-of-view demand without spectacles. No physiologic complications such as edema or neovascularization were observed during the follow-up period. CONCLUSIONS: This new soft lens design for irregular corneas is especially indicated for those with intolerance to RGP or other contact lenses and for patients for whom RGP lenses do not satisfy the dynamic environment inherent to some professional or leisure activities, particularly sport activity. This is a good option to consider in patients with mild to moderate keratoconus and good correction of slight or moderate irregular corneal astigmatism with good tolerance. Aftercare implications are also discussed.